Using economic data to demonstrate the value of the library - Lamont, Melissa (Qualitative and Quantitative Methods in Libraries, 2017)
Libraries have always collected data from the number of books to the number of web page views.  These statistics do not give a complete accounting of the library’s value.  To fully demonstrate the value of libraries, and justify budgets, librarians have increasingly turned to economic valuations.  Yet, economic valuations are challenging for non-profit, cultural and educational institutions.  This paper reviews the positive and negative aspects of economic valuation for libraries.